Implementasi Model Pembelajaran yang Digunakan oleh Guru PJOK pada Masa New Normal di Kelas XI SMA Negeri 1 Gombong - Negara, Saj Kusuma; Qoriah, Anirotul (Indonesian Journal for Physical Education and Sport, 2023)
Entering the New Normal period in various regions in Indonesia affects teaching and learning in senior high schools. The research problem is the implementation of the learning model used by PJOK teachers during the New Normal period in Class XI of SMA Negeri 1 Gombong. The purpose of this study was to describe the implementation of the PJOK learning model, the inhibiting and supporting factors during the New Normal period. Data collection techniques were carried out by means of observation, interviews and documentation. The results showed that the implementation of the PJOK learning model which was applied in class XI SMA Negeri 1 Gombong used a learning model by adjusting to the learning system due to new normal conditions. which is delayed due to taking turns, time constraint, and lack of student character. Supporting factors ranging from quota assistance, school facilities, vaccinations, health protocols, teacher ability and student motivation in learning. The conclusion is the implementation of the learning model used to adapt to the learning system used by school.